2008
DOI: 10.1063/1.2908872
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-limited mass flow of liquid He3

Abstract: We consider theoretically the possibility of observing unusual quantum fluid behavior in liquid 3 He and solutions of 3 He in 4 He systems confined to nano-channels. In the case of pure ballistic flow at very low temperature conductance will be quantized in units of 2m 2 /h. We show that these steps should be sensitive to increases in temperature. We also use a random scattering matrix simulation to study flow with diffusive wall scattering. Universal conductance fluctuations analogous to those seen in electro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…For very dilute mixtures at the lowest temperatures, 3 He behaves like an ideal Fermi gas with a very long mean free path of several tens of micrometers. An array of nanopores was then proposed as a connection between two tanks of helium, with holes on the order of 10 nm, which is compatible with the Fermi wavelength of 3 He [135,136].…”
Section: Other Neutral Particlesmentioning
confidence: 99%
“…For very dilute mixtures at the lowest temperatures, 3 He behaves like an ideal Fermi gas with a very long mean free path of several tens of micrometers. An array of nanopores was then proposed as a connection between two tanks of helium, with holes on the order of 10 nm, which is compatible with the Fermi wavelength of 3 He [135,136].…”
Section: Other Neutral Particlesmentioning
confidence: 99%
“…Future experiments will focus on reducing the size of the nanofluidic channel even further, towards the one-dimensional limit [19,20], where quantum ballistic transport should give rise at low temperatures to a conductance quantized in the unit of G m ¼ 2m 2 =h, the quantum of conductance for mass flow.…”
mentioning
confidence: 99%
“…In conclusion, we have made a direct observation of the smooth crossover between the collective transport of particles emanating from a continuum to a single-particle statistical flow occurring in a single nanohole. Future experiments will focus on reducing the size of the nanofluidic channel even further, towards the one-dimensional limit [19,20], where quantum ballistic transport should give rise at low temperatures to a conductance quantized in unit of G m = 2m 2 /h, the quantum of conductance for mass flow.…”
mentioning
confidence: 99%
“…Both will be referred to as f in their respective contexts, with chemical potentials μ L and μ R , referring to the left and right side of the channel, where (μ L − μ R ) = mΔP/ (ρ). Transport from the left to right is defined as positive in quantized units of G where [22]:…”
Section: Quantum Noisementioning
confidence: 99%
“…The noise, δQ, will be calculated as a mean squared fluctuation, 〈δQ 2 〉, where 〈...〉 refers to an average with respect to time. Recent work found that G is quantized in units of 2m 2 /h, where m is the mass of a fluid particle and h is Planck's constant [22,23]. The resemblance with the quantum of electrical conductance (2e 2 /h where e is the electrical charge) highlights the close analogy between mass flow and charge flow.…”
Section: Introductionmentioning
confidence: 99%